Diagnosis and treatment of craniosynostosis: Vilnius team experience - Zaleckas, Linas; Neverauskienė, Arijanda; Daugelavičius, Vidūnas; Šidlovskaitė-Baltakė, Dominika; Raugalas, Ramūnas; Vištartaitė, Berta; Balčiūnaitė, Evelina (Acta medica Lituanica, 2015)
Background. The aim of the study was to review the methods of diagnosis of craniosynostosis and to analyze Vilnius (Lithuania) team experience of surgical treatment, surgical methods, aspects of anesthesia for patients with craniosynostosis and to present early results of surgical treatment. Materials and methods. A retrospective review of all patients with various types of craniosynostosis treated surgically during the period from 1 January 2009 to 31 December 2014 was performed. The following data were analyzed: age, type of deformity, surgical technique, surgical time, methods and course of anesthesia, intra- and postoperative complications, parents’ satisfaction, head form. Results. 24 patients were treated. The mean patient’s age at the time of surgery was 13.47 ± 8.2 months (min 7.3, max 46.5). Eliminating 3 patients whose age at the time of surgery was over 2 years (24.5, 29 and 46 months, respectively), the mean age of other 21 patients was 10.63 ± 1.77 (min 7.3, max 14.1) months. There were 9 cases of isolated trigonocephaly (37.5%), 7 cases of isolated scaphocephaly (29.2%), 7 cases of isolated anterior plagiocephaly (29.2%) and 1 case of posterior plagiocephaly combined with scaphocephaly (4.17%). All craniosynostoses were diagnosed clinically and diagnosis was confirmed with computed tomographic scanning. The median duration of surgery was 336.47 ± 59.63 minutes (min 308.13, max 364.82). The medium stay in the intensive care unit was 2.53 ± 1.28 days (min. 1.92, max 3.14). In all cases rigid osteosynthesis was performed. 2 children were diagnosed with syndromic craniofacial abnormalities. In 23 (95.83%) cases an intraoperative or postoperative blood transfusion was required. In 24 treated patients there was no mortality. During the early and late postoperative period no infections, CSF leakage and dural tears were observed. No neurological impairments or any signs of neurological deficits were observed by any of the treated patients. In all of cases parents were satisfied with their children’s changed head shape and aesthetic results. Conclusions. Cranioplasties for correction of craniosynostosis give good aesthetic results and this is a safe method, which helps to correct the head shape as well as improves the social adaptation of patients.